2015
DOI: 10.1038/bcj.2015.68
|View full text |Cite
|
Sign up to set email alerts
|

T-cell ligands modulate the cytolytic activity of the CD33/CD3 BiTE antibody construct, AMG 330

Abstract: Preclinical and emerging clinical studies demonstrate that bispecific T-cell engaging (BiTE) antibody constructs can potently lyse targeted tumor cells, but the determinants for their activity remain incompletely understood. Using human acute myeloid leukemia (AML) cell lines engineered to overexpress individual T-cell ligands, we found that expression of the inhibitory ligands, PD-L1 and PD-L2, reduced the cytolytic activity of the BiTE antibody construct targeting CD33, AMG 330; conversely, expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…These analyses demonstrated that the TandAbs not only activated T-lymphocytes but also re-directed polyclonal T cells from healthy donors as well as autologous T cells from patients with AML to effectively lyse CD33 þ AML cells even at low E:T cell ratios. The anti-AML effect of these TandAbs was dependent on antibody concentration and E:T cell ratio, and required the presence of both T cells and CD33 þ target cells-mechanistic determinants that are similar to those identified recently for small CD33/CD3-directed bispecific antibodies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Importantly the TandAbs' avidity of CD3 and CD33 strongly influenced the degree of cytotoxic activity in that, for high antileukemia potency, high avidity to both CD33 and CD3 was required.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…These analyses demonstrated that the TandAbs not only activated T-lymphocytes but also re-directed polyclonal T cells from healthy donors as well as autologous T cells from patients with AML to effectively lyse CD33 þ AML cells even at low E:T cell ratios. The anti-AML effect of these TandAbs was dependent on antibody concentration and E:T cell ratio, and required the presence of both T cells and CD33 þ target cells-mechanistic determinants that are similar to those identified recently for small CD33/CD3-directed bispecific antibodies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Importantly the TandAbs' avidity of CD3 and CD33 strongly influenced the degree of cytotoxic activity in that, for high antileukemia potency, high avidity to both CD33 and CD3 was required.…”
Section: Discussionsupporting
confidence: 52%
“…S1 for analytic strategy; refs. 13,16,17). After 48 hours, cell numbers and viability, using DAPI to detect non-viable cells, were determined using a LSRII cytometer (BD Biosciences) and analyzed with FlowJo.…”
Section: Quantification Of Tandab-induced Cytotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, AMG330, a CD33/CD3-directed bispecific T-cell engager antibody (BiTE; refs. [10][11][12][13], has entered clinical testing and chimeric antigen receptors T-cell approaches (CAR-T) are additionally feeding the pipeline for the treatment of AML (14,15). All of these immunotherapeutic agents are targeting the sialoadhesin receptor CD33 (Siglec-3), a 67-kDa protein, expressed on leukemic blasts of AML patients (16).…”
Section: Introductionmentioning
confidence: 99%